2020
DOI: 10.1038/s41398-020-00955-7
|View full text |Cite|
|
Sign up to set email alerts
|

Cortisol reactivity in patients with anorexia nervosa after stress induction

Abstract: There is a need of experimental studies on biomarkers in patients with anorexia nervosa (P AN), especially in the context of stress, in order to foster understanding in illness maintenance. To this end, the cortisol response to an acute stressor was investigated in n = 26 P AN (BMI: 19.3 ± 3.4 kg/m 2), age, and gender matched to n = 26 healthy controls (HC; BMI: 23.08 ± 3.3 kg/m 2). For this purpose, salivary cortisol parameters were assessed in two experimental conditions: (1) rest/ no intervention and (2) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 115 publications
0
17
0
Order By: Relevance
“… 44 , 45 , 46 Although the irrational fear of excessive body mass persists or even grows regardless of body weight and weight loss during starvation, 47 some aspects of anxiety (e.g., blushing during public speaking) seem to diminish during acute starvation. 48 , 49 , 50 This may be caused by a shift of attention toward eating and body weight concerns and away from social issues. 51 , 52 Thus, the anxiolytic effect of starvation seen in the animal model can only partly be confirmed in clinical observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 44 , 45 , 46 Although the irrational fear of excessive body mass persists or even grows regardless of body weight and weight loss during starvation, 47 some aspects of anxiety (e.g., blushing during public speaking) seem to diminish during acute starvation. 48 , 49 , 50 This may be caused by a shift of attention toward eating and body weight concerns and away from social issues. 51 , 52 Thus, the anxiolytic effect of starvation seen in the animal model can only partly be confirmed in clinical observations.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of anxiety can thus be considered as a decisive factor leading to the maintenance of self‐starvation 44–46 . Although the irrational fear of excessive body mass persists or even grows regardless of body weight and weight loss during starvation, 47 some aspects of anxiety (e.g., blushing during public speaking) seem to diminish during acute starvation 48–50 . This may be caused by a shift of attention toward eating and body weight concerns and away from social issues 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…Elevated baseline cortisol levels are likely observed during extreme caloric restriction in both healthy individuals and patients with AN. However, reversibility of HPAA dysregulation, even in recovered patients with AN, is not always observed [34]. Cortisol stimulates gluconeogenesis, and cortisol levels in patients with AN have been shown to be inversely correlated to fasting glucose [35].…”
Section: Hypothalamic-pituitary-adrenal Axismentioning
confidence: 99%
“…The visual analog scale for perceived control (PC) and the PANAS were immediately completed. Further, as previous studies have reported that the peak salivary cortisol levels would appear around 10-20 min after cessation of the TSST (Kirschbaum et al, 1993;Langer et al, 2020;Keenan et al, 2021; for a review, see Kudielka et al, 2007), saliva samples were collected four times at 0, 20, 45, and 60 min after the TSST as referred to measurement settings of previous studies using the TSST as the acute stressor (Johnson et al, 2019;Schmalbach et al, 2020; Figure 1).…”
Section: General Proceduresmentioning
confidence: 99%